Migrasi dan Problematika Minoritas Muslim di Negara-Negara Barat - Kusumowardhani, Indriyani (Jurnal Keislaman, 2024)
Migration of Muslims to the west often faces a clash of civilizations. Therefore, the question from this research is how Muslim immigrants face the challenges of minority problems in Western countries, what policies have been made by Western countries as a solution to the clash of civilizations? The research uses qualitative methods through literature research which can provide a deeper understanding of the dynamics of migration and its problems. The findings from this research are that several Western countries have made policies that teach the principles of inclusivity, plurality and respect for all individuals and cultures. And the most obvious answer is "coexistence" despite having completely different beliefs, behaviors, habits and outward appearances.